2020
DOI: 10.1016/j.eswa.2019.112880
|View full text |Cite
|
Sign up to set email alerts
|

A compositional model of multi-faceted trust for personalized item recommendation

Abstract: We propose a compositional recommender system based on multi-faceted trust.• The trust model is based on social links and global feedback about users.• The recommender can work with or without using information about social relations.• We validate our recommendation model on two public datasets of item reviews.• Our recommender outperforms state-of-the-art trust-based recommender systems. AbstractTrust-based recommender systems improve rating prediction with respect to Collaborative Filtering by leveraging the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…Lee et al [17] proved that users' evaluations are affected by other users and that users connected by a network of trust exhibit significantly higher similarity on items. Ardissono et al [18] proposed a compositional recommender system based on multi-faceted trust using social links and global feedback about users. Jaehoon et al [19] proposed a new trust recommendation algorithm, TCRec.…”
Section: Related Workmentioning
confidence: 99%
“…Lee et al [17] proved that users' evaluations are affected by other users and that users connected by a network of trust exhibit significantly higher similarity on items. Ardissono et al [18] proposed a compositional recommender system based on multi-faceted trust using social links and global feedback about users. Jaehoon et al [19] proposed a new trust recommendation algorithm, TCRec.…”
Section: Related Workmentioning
confidence: 99%
“…Liu et al [10] proposed a model that takes into account the local contextual information of user ratings and the global preferences of user behaviors.This model solved the problem of inaccurate trust evaluation caused by low user ratings, and can improve recommendation performance.In order to protect the privacy of users, and to consider as much evidence as possible, using limited information to predict the trust value of users is now required to be resolved. Liliana Ardissono et al's [11]trust-based recommendation system adds evidence of trust on the basis of publicly anonymous information, that is, personal contribution quality and multi-dimensional global reputation. Xin Wang et al [12] combined neural network methods and Dempster-Shafer theory to study trust and distrust.…”
Section: Related Workmentioning
confidence: 99%
“…They noticed that those trustors who follow the same trustee, having similar tastes and shared common features that improve the performance of socialbased recommendations [103]. Ardissono proposed a LOCABAL+ model that is a trust-based recommendation model by defining a multifaceted trust by users feedback and generated top N recommendations [108]. Noh et al developed a trust aware model and studied the impact of power users available in social networks and exploited the trust cluster and observed that clusters with normal user provided better results [104].…”
Section: Ctrust-based Recommendation Systemsmentioning
confidence: 99%